(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2017)
This paper investigates the modeling of the Reactive Powder Concrete (RPC) beams reinforced with the different types of the reinforcement (steel and Sand-coated CFRP). The ANSYS 11 program was used. The experimental works included casting of eight RPC concrete beams. Four of them reinforced with steel bars, while the others were casted using sand-coated CFRP bars. The mechanical properties of the RPC were experimentally obtained. The manufacturing data were used for CFRP bars. The RPC was modeled by Solid 65 element. The steel plate for loading and support was modeled by. The steel and CFRP Bars were modeled by discrete bar element. The study includes the effect of the distribution of the steel fibers on the flexural behavior in term of load-deflection relation. The uniformly distributed of the steel fiber longitudinally and vertically gave the best behavior than the corresponding experimental results for both types of reinforcements.